Impact of Work Spirituality, Leadership, Management Support, and Competence on Employee Performance: The Role of Organizational Climate at Baznas - Agustina, Lutvi Sri; Efendi, Suryono; Sugiono, Edi (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
This study aims to analyze the effect of work spirituality, integrative leadership, management support, and competence on employee performance at BAZNAS (national amil zakat agency) with organizational climate as an intervening variable. This study uses a survey method by distributing questionnaires to BAZNAS employees. Quantitative research method with SEM analysis technique with AMOS version 22 application. The sample in this study were 145 respondents. The results showed that work spirituality, integrative leadership, management support, and competence directly had a positive and significant effect on employee performance at BAZNAS. Work spirituality directly has a positive and insignificant effect on employee performance. Integrative leadership directly has a positive and insignificant effect on employee performance.